Atmospheric Chemistry in the Mediterranean Region 2022
DOI: 10.1007/978-3-030-82385-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol and Tropospheric Ozone Direct Radiative Impacts

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 130 publications
0
1
0
Order By: Relevance
“…Satellite observations and in-situ measurements have also been used to show that desert dust aerosols might also suppress precipitation in marine clouds (Rosenfeld et al 2001;Mahowald and Kiehl 2003). The latter two studies found a strong relationship between thin cloud properties and mineral dust concentrations over North Africa.…”
Section: The Case Of Dust Particlesmentioning
confidence: 99%
“…Satellite observations and in-situ measurements have also been used to show that desert dust aerosols might also suppress precipitation in marine clouds (Rosenfeld et al 2001;Mahowald and Kiehl 2003). The latter two studies found a strong relationship between thin cloud properties and mineral dust concentrations over North Africa.…”
Section: The Case Of Dust Particlesmentioning
confidence: 99%